Swallowing apraxia in a patient with recurrent ischemic strokes: A case report. Issue 39 (September 2019) - Yun, Yeo Joon; Na, Yong Jae; Han, Seung Hoon
Abstract: Rationale: Swallowing apraxia is defined as dysfunction in oral phase caused by the deficit in the coordination of tongue, lip, and chin movements, without motor weakness, sensory loss, and cognitive decline and has not been reported yet. Patient concerns: A 69-year-old male with personal medical history of ischemic stroke about 10 years ago newly developed right striatocapular infarction. He had a problem in the oral phase of swallowing after recurrent ischemic strokes. Diagnoses: He was diagnosed as swallowing apraxia via bed side examination and videofluoroscopic swallowing study. Intervention: Videofluoroscopic swallowing study was done in this case. Outcomes: Symptoms and findings of VFSS were not improved after 2 months treatment. Lessons: This case implies that a clinician should be alert to swallowing apraxia as a possible cause when a patient with recurrent strokes complains of oral phase dysfunction of swallowing and considers proper diagnostic option such as videofluoroscopic swallowing study.